Bulk Microforming from Sheet Metal—A Promising Approach for the Mass Production of Cold-Formed Metallic Micro Parts - Kraus, Martin; Merklein, Marion (Minerals, Metals and Materials Series, 2021)
Every year billions of micro parts are produced. In mass production, cold bulk forming offers considerable technological, economical, and ecological potentials compared to alternative production methods. Due to the occurrence of scale effects, high tool stresses, and handling problems, cold bulk forming is not used for the mass production of multi-stage formed metallic micro parts. Within this paper, multi-stage bulk microforming from sheet metal is investigated on the laboratory scale with the material Cu-OFE. Throughout this process, the sheet metal strip serves both as a semi-finished product and as a handling aid. In the first forming stage, a pin is extruded from sheet metal, which is then extruded in a cup during the second stage. For the identification of size effects and the evaluation of such effects on the part quality, the tests are carried out on macro- and micro-scale. In the first step, the process-influencing variable of the blank holder pressure is investigated in the first forming stage in order to derive measures for the highest possible material utilization. The two-stage forming of the pin with cup is compared with a single-stage process to assess the part quality and material utilization depending on the process strategy. Using the correct geometric scaling, size effects are identified and their effects on the forming process are evaluated. The experimental results reveal that it is possible to fabricate micro parts with a diameter of 470 µm and a minimum wall thickness of 36 µm reproducible by using the presented cold bulk microforming process strategy.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Bulk microforming; Material flow; Metallic micro parts; Pin extrusion; Sheet metal; Size effects